Interaction of the pioneer transcription factor GATA3 with nucleosomes - Hiroki Tanaka (Nature Portfolio, 2020)
GATA 3 functions as a pioneer factor during cellular reprogramming. Here the authors delineate nucleosome positioning relative to GATA3 binding motifs and describe the structure of a GATA3–nucleosome complex; providing insight into how a pioneer factor interacts with nucleosomes and catalyze their local remodelling to produce an accessible enhancer.